(untitled) (Research, Society and Development, 2020)
To determine the prevalence of possible drug-nutrient interactions in hospitalized patients undergoing enteral nutritional therapy and to analyze the clinical risk. Observational, analytical and retrospective study with medical records of 104 patients undergoing enteral nutritional therapy, admitted to a university hospital in a capital of southern Brazil. Information was collected in the electronic medical record Tasy®, from patients hospitalized from July to December 2018, who received enteral nutritional therapy. The drugs used were classified according to the Anatomical Therapeutic Chemical Code. Drug-nutrient interactions were determined using the Micromedex 2.0® program. Of the 112 medications used by patients, 28.6% of potential prevalence of drug-nutrient interactions was observed, with 6.25% of potential for drug interaction with food in general and 2.7% of potential for interaction with enteral nutritional therapy, of moderate severity (n = 19; 59.4%), with a good level of evidence (n = 17; 53.2%) and of immediate onset (n = 22; 68.7%). The drugs involved were mainly phenytoin, levothyroxine and warfarin. Patients undergoing enteral nutritional therapy have a small but harmful risk of drug-nutrient interactions, mainly related to the treatment of seizure crises, thyroid, and blood clotting. It is suggested that protocols be implemented in order to ensure nutritional and drug safety for hospitalized patients.